Alternative Tourism and Shared Accommodation Motivation: a cross-national study - Rodas Vera, Luciana Alves; Gosling, Marlusa de Sevilha; Silva, João Albino; Coelho, Mariana de Freitas (Almatourism - Journal of Tourism, Culture and Territorial Development, 2024)
CouchSurfing is a non-profit internet site through which people offer or get free lodging in the host’s home. The aim of the current article is to compare the various motivations of sharing behaviours occurring amongst Brazilian and Portuguese when guests, as far as the use of Couchsurfing as an alternative tourism activity is concerned. The current study offers a qualitative, exploratory and comparative approach addressing Brazilian and Portuguese guests. The results rely on 18 in-depth interviews with ten Brazilian and eight Portuguese guests. The content analysis was carried out based on theme categorization defined before data collection. As far as the similarities between the guests from both countries is concerned, the expectations of sharing cultural experiences and establishing social bonds, as well as the need to trust the host indicated the motivation to travel using the platform - this included both parties, the Portuguese and the Brazilians alike. Conversely, only the Brazilians indicated the motivation of use as means of reducing travel costs and meeting utilitarian needs such as sleeping. The study contributes to the sharing economy literature as it identifies that the Degree of Identification amongst the Peers, Perceived Risks, and Value Co-creation Perception are also elements that motivate sharing tourism.